1984
DOI: 10.1159/000260748
|View full text |Cite
|
Sign up to set email alerts
|

Lower Fluoride Concentrations for Topical Application

Abstract: The potential toxicity of fluoride application can be reduced by using lower fluoride concentrations. A previous study has shown that 0.4% F–– and 1.2% F–– organic fluoride gels were equally effective in preventing demineralization in both sound and primed human enamel. In this study 0.4, 0.1 and 0.01 % F–– amine fluoride and acidulated phosphate fluoride (APF) solutions were tested to see whether a further reduction in concentration was possible. All amine fluoride groups and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…According to the modern concept, the caries preventive effect of fluoride is based on promotion of remineralization by small amounts of fluoride at the plaqueenamel interface rather than on an increase in the fluoride content of enamel, the latter requiring relatively high concentrations of fluoride (4). According to several studies, the eflicacy of a fluoride regimen in enamel remineralization or caries inhibition does not increase proportionally with increasing concentration of fluoride in the preparation (7)(8)(9)(10)(11). In previous studies, the caries preventive effect of two fluoride varnishes did not continue after applications were discontinued, even though the fluoride content of enamel remained high (5)(6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the modern concept, the caries preventive effect of fluoride is based on promotion of remineralization by small amounts of fluoride at the plaqueenamel interface rather than on an increase in the fluoride content of enamel, the latter requiring relatively high concentrations of fluoride (4). According to several studies, the eflicacy of a fluoride regimen in enamel remineralization or caries inhibition does not increase proportionally with increasing concentration of fluoride in the preparation (7)(8)(9)(10)(11). In previous studies, the caries preventive effect of two fluoride varnishes did not continue after applications were discontinued, even though the fluoride content of enamel remained high (5)(6).…”
mentioning
confidence: 99%
“…This suggests that increased fluoride concentration of enamel is not the main caries preventive mechanism of the varnishes. According to several studies, the eflicacy of a fluoride regimen in enamel remineralization or caries inhibition does not increase proportionally with increasing concentration of fluoride in the preparation (7)(8)(9)(10)(11). Moreover, DIJKMAN et al (12) found no difference in fluoride uptake by enamel from APF gels containing 0.11-1.23% fluoride.…”
mentioning
confidence: 99%
“…Topical fluoride (F), in various forms, is effective in preventing dental caries [Brown and König, 1977;Ericsson, 1978;Wei, 1985], Recent in vitro evidence indi cates that there is no direct correlation between the F contents of topical F agents and their ability to (1) release F [Congleton et al" 1978;Hattab and Linden, 1985]; (2) reduce enamel solubility [Shrestha et al, 1972;Shannon and Ed monds, 1978;Hattab, 1984a]; (3) decrease the carious lesion depth [Sluiter and Purdell-Lewis, 1984], and (4) increase enamel F uptake from APF gels [Dijkman et al, 1982;Naleway, 1985], Abrasive and acid-etch sampling tech niques have been employed to measure the uptake and penetration of F in enamel fol lowing treatment with different F agents. Enamel sampling based on acid etch is practical and provides reliable data, as suming that the dissolved F, calcium and phosphate in the etching solution were de rived from fluoridated apatite [Wei et al, 1976;Berndt and Stearns, 1978].…”
mentioning
confidence: 99%